1993
DOI: 10.1108/eb037820
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Conducting Adhesives for Electronic Interconnection

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Comparing the result with the ratio of ten obtained using other models (Yim and Paik 1998;Hu et al 1997;Shi et al 1999;Williams et al 1993), the proposed scheme predicts much more accurately. The main reason for the improvement is that the route of the gold bumps, which contributes most to the equivalent resistance, is taken into consideration.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Comparing the result with the ratio of ten obtained using other models (Yim and Paik 1998;Hu et al 1997;Shi et al 1999;Williams et al 1993), the proposed scheme predicts much more accurately. The main reason for the improvement is that the route of the gold bumps, which contributes most to the equivalent resistance, is taken into consideration.…”
Section: Resultsmentioning
confidence: 52%
“…The gap between the experiment and the prediction implies that except for the compressive load, there are some unmodeled properties that affect the contact resistance. Chin et al (2004) compared different models (Yim and Paik 1998;Hu et al 1997;Shi et al 1999;Williams et al 1993) used in estimating the contact resistance of anisotropic conductive adhesive assemblies. It was found that there are great inconsistencies among the current models and between the predicted contact resistances and the experimentally measured values.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have reported the deformation effect on the electrical conduction development during the ACA assembly. The first publication is from Williams, et al [19] and the contact resistivity ρ of an ACA joint was estimated as:…”
Section: Electrical Conduction Development and Residual Stressesmentioning
confidence: 99%
“…Furthermore, because of recent innovation of IC packaging technology, high density and high performance interconnection method has become essentially important. As a result, flip chip technology gains attractiveness as one of the best chip packaging candidates to meet recent technical trends [1][2][3].…”
Section: Introductionmentioning
confidence: 99%